ПЛИН МАСТИЛА У ВУЗЬКІЙ КЛИНОПОДІБНІЙ ЩІЛИНІ З РУХОМОЮ СТІНКОЮ - Avramenko, A.A.; Tyrinov, A.I.; Kovetskaya, M.M.; Kondratieva, E.A. (Institute of Engineering Thermophysics of NAS of Ukraine, 2023)
The article presents the results of a study of the lubricant flow in a narrow wedge-shaped slot with a movable wall. A solution to the problem with slip boundary conditions on the channel walls is obtained. The effect of slippage on the change in hydrostatic lift and hydraulic resistance in the slotted channel is shown.  It was determined in the work that with an increase in the slip intensity (an increase in the value of the Knudsen number), the pressure variation weakens.  This is due to the weakening of the interaction of the flow with the wall. As a result, the hydraulic resistance is reduced. The dependence of the relative hydrostatic lifting force on the Knudsen number and the opening angle of the channel is obtained. It is determined that with an increase in the Knudsen number, the magnitude of the hydrostatic lifting force decreases, since the influence of the flow on the wall weakens. The influence of slippage weakens with an increase in the opening angle of the channel.